ANALISIS INDEKS KEPUASAN MASYARAKAT PADA UPTD TERMINAL TIRTONADI DLLAJ KOTA SURAKARTA - -, Mulyanto (Universitas Slamet Riyadi, 2007)
Abstract The Determination of Surakarta’s District Government in giving fine service in the field of public service is marked by the development of UPTD. Tirtonadi Bus Station of DLLAJ Surakarta’s District is measurement as institution who gave best service if the process works fast, appropriate, and definite. Based on the analysis towards score of service index UPTD Tirtonadi Bus Station of DLLAJ Surakarta’s District is 2.84. Conversed with the basic score of 25 the result is 70,9645. Based on Those calculations, quality service of UPTD Tirtonadi Bus Station of DLLAJ Surakarta’s District is considered as B, meaning that service performance of UPTD Tirtonadi Bus Station of DLLAJ Surakarta’s District is good. Even the overall services are fair, however researcher recommended the service appropriateness are considered time wasted and circumlocutory to the public. Keywords: society satisfaction index, service quality